Development and characterization of 26 novel microsatellite loci for the trochid gastropod Gibbula divaricata (Linnaeus, 1758), using Illumina MiSeq next generation sequencing technology - Violeta López-Márquez; Ricardo García-Jiménez; José Templado; Annie Machordom (PeerJ, 2016)
In the present study we used the high-throughput sequencing technology Illumina MiSeq to develop 26 polymorphic microsatellite loci for the marine snail Gibbula divaricata. Four to 32 alleles were detected per locus across 30 samples analyzed. Observed and expected heterozygosities ranged from 0.130 to 0.933 and from 0.294 to 0.956, respectively. No significant linkage disequilibrium existed. Seven loci deviated from Hardy-Weinberg equilibrium that could not totally be explained by the presence of null alleles. Sympatric distribution with other species of the genus Gibbula, as G. rarilineata and G. varia, lead us to test the cross utility of the developed markers in these two species, which could be useful to test common biogeographic patterns or potential hybridization phenomena, since morphological intermediate specimens were found.